Peer Review in Health Sciences. - Godlee, Fiona (Blackwell Pub., 2003)
This work discusses the state of peer review, questions its role in the changing world of electronic journal publishing, and debates where it should go from here. New chapters have been added on qualitative peer review, training, consumers, and innovation.